The Influence Of Job Placement, Career Development And Coordination On The Work Performance Of Employees Of The Muara Enim District Health Office - Nofi Heryani; Hardiyansyah Hardiyansyah; Emi Suwarni (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of job placement, career development, and coordination individually and together on the work performance of employees of the Muara Enim Regency Health Office. The research method used in this research is quantitative method using questionnaires distributed to respondents. Test data quality using validity test, reliability test. The data analysis technique used is Structural Modeling Equation (SEM) from the AMOS statistical software package used in hypothesis testing. The results of descriptive research to describe the perceptions of respondents on each variable can be concluded that: Respondents' perceptions of the employee Job Placement variable at the Muara Enim Regency Health Office are relatively good. Respondents' perceptions of employee career development variables at the Muara Enim Regency Health Office are relatively good. Respondents' perceptions of employee coordination variables at the Muara Enim Regency Health Office are relatively good. Respondents' perceptions of employee Work Achievement variables at the Muara Enim Regency Health Office are relatively good. Factors that affect employee work performance at the Muara Enim Regency Health Office are job placement and coordination, while career development has no direct effect on work performance.